(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents a novel neutrosophic Agricultural Topology based MCDM approach for solving decision-making problems in agriculture, with uncertainties and infinite variables. Neutrosophic sets are introduced to formalize uncertainties and the neutrosophic sub-base can produce a topology for a dual study of the issue via open sets. The work analyses further properties of the neutrosophic hypersoft(NH) topology; basis, subspace, interior, and closure properties. Two algorithms are proposed: one employing NH sets and the other employing NH topology. Numerical examples derived from real-life agriculture situations prove the usefulness of this approach in increasing the efficiency of choice-making strategies.